The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3324/haematol.2016.147900
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib for relapsed/refractory chronic lymphocytic leukemia: a UK and Ireland analysis of outcomes in 315 patients

Abstract: I n 2014, ibrutinib was made available for relapsed/refractory chronic lymphocytic leukemia patients. The UK Chronic Lymphocytic Leukaemia Forum collected data from UK/Ireland patients with a minimum of 1 year follow-up with pre-planned primary endpoints; the number of patients still on therapy at 1 year "discontinuation-free survival" and 1 year overall survival. With a median of 16 months follow up, data on 315 patients demonstrated a 1 year discontinuation-free survival of 73.7% and a 1 year overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
63
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 8 publications
17
63
3
Order By: Relevance
“…The present analyses focus on patients with early incomplete adherence and possibly represents a group that is at greater risk of poor adherence and subsequent poor outcomes. Despite our results and those obtained within the context of a clinical trial 3 demonstrating transient disease progression related to temporary dose holds, this appears to be reversible with re-initation of therapy 16 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present analyses focus on patients with early incomplete adherence and possibly represents a group that is at greater risk of poor adherence and subsequent poor outcomes. Despite our results and those obtained within the context of a clinical trial 3 demonstrating transient disease progression related to temporary dose holds, this appears to be reversible with re-initation of therapy 16 .…”
Section: Discussioncontrasting
confidence: 99%
“…This would suggest that the ideal treatment strategy would be to recommend initiation of therapy at standard dosing and interruption as needed as directed in the FDA label. Two studies have reported no negative impact for patients requiring dose reductions 16, 17 , however differences may be attributable to population differences and timing of reductions. The present analyses focus on patients with early incomplete adherence and possibly represents a group that is at greater risk of poor adherence and subsequent poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a real‐world study of ibrutinib‐treated patients enrolled in a compassionate‐use programme, the estimated 10‐month PFS and OS rates were 71% and 78%, respectively, for 50 patients with del(17p) (Winqvist et al , 2016). In a real‐world study of ibrutinib‐treated patients in a named patient scheme, the estimated 12‐month discontinuation‐free progression and OS rates were 71% and 84%, respectively for 90 patients with del(17p) (UK CLL Forum 2016). Together, the results of these clinical trials and real‐world analyses support the conclusion that ibrutinib is among the most active agents yet developed for the treatment of del(17p) CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial study, many more patients with del(17p) CLL have been treated with ibrutinib, including in real‐world settings (Mato et al , 2016, UK CLL Forum 2016; Winqvist et al , 2016). To provide a more robust description of outcomes in the prospective trials in this important high‐risk patient population, we conducted a combined analysis of 243 patients with R/R del(17p) CLL who received treatment with single‐agent ibrutinib (420 mg) in 1 of 3 prospective clinical studies (Byrd et al , 2013, 2014, 2015; O'Brien et al , 2014, 2016a).…”
mentioning
confidence: 99%
“…Despite, the well characterized toxicity profile of the drug, analysis of clinical trials and real-world data revealed that in particular patient cohorts, up to approximately 30% patients discontinue ibrutinib therapy due to toxicity [57,61,62,[73][74][75][76]].…”
Section: Ibrutinib Adverse Eventsmentioning
confidence: 99%